Photoinactivation of MRSA on skin: effect of potassium iodide and iodopovidone as potentiators of a porphyrinic formulation - Braz, Márcia Alexandra Dias (2021)
Staphylococcus aureus, Gram-positive bacterium, is one of the leading causes of a wide range of serious clinical infections, such as skin and soft tissue infections. To treat these infections, antibiotics are used as the first treatment option. However, S. aureus, namely methicillin-resistant S. aureus (MRSA), can acquire resistance to the conventionally used antibiotics. This fact is associated with high mortality, morbidity and high financial costs associated with the treatment. Therefore, new approaches for the control of infections by this bacterium are needed. Antimicrobial photodynamic therapy (aPDT), a multitarget therapy, has emerged as a promising alternative treatment for localized infections in response to the growing problem of antibiotic resistance. This therapy requires the use of three key elements: photosensitizer (PS), light (usually in the visible range) and oxygen. In the presence of these elements reactive oxygen species (ROS) responsible for oxidative damage and microbial cell death, are generated. Despite several in vitro studies reporting the effectiveness of this therapy in inactivating a broad spectrum of microorganisms, including S. aureus, there are few in vivo and ex vivo studies. In this sense and given the importance of the composition of test matrices in aPDT, in order to transpose this therapy for clinical application, it is necessary to test the PSs in clinically relevant matrices. Thus, the aim of this work was to evaluate the effectiveness of various aPDT approaches to control S. aureus infections on skin. The use of aPDT adjuvants is important in order to increase the efficiency of aPDT, reducing at the same time the amount of PS and/or the treatment time and therefore the costs involved. In this work, a porphyrin formulation (FORM), based on a non-separated mixture of 5 cationic porphyrins and with recognized efficiency as an alternative to the highly efficient PSs included in the formulation was used, in order to reduce the costs and synthesis time relatively to the use of the separated porphyrins. FORM has already been shown to be effective in aPDT of various bacteria, including S. aureus. Potassium iodide (KI), recognized for increasing the efficiency of some PSs in a broad spectrum of microorganisms, including S. aureus, through the formed iodine species, was also used as a potentiator of aPDT. Iodopovidone (PVP-I), a commonly used antimicrobial agent as disinfectant and antiseptic, being a water-soluble complex of iodine bound to polyvinylpyrrolidone, was also tested as a potentiator of aPDT. In a first phase, the aPDT protocol was developed in phosphate buffered saline (PBS, in vitro). Thereafter, the efficacy of FORM, as PS, alone and in combination with KI or PVP-I to photoinactivate MRSA on skin was evaluated. For this, porcine skin (considered a good test model for human skin) was artificially contaminated with MRSA and treated with FORM, FORM + KI or FORM + PVP-I, under white light. The results showed that FORM was effective to inactivate MRSA in PBS, where total inactivation was achieved for all tested concentrations (0.5, 1.0 and 5.0 μM). For the combinations FORM + KI and FORM + PVP-I, total inactivation of MRSA and considerable reduction in irradiation time compared to FORM alone was observed using the lowest tested PS concentration (0.5 μM). On skin, ex vivo, a reduction in MRSA survival of 3.1 Log10 colony forming units (CFU) mL-1 with 50 μM FORM, was observed. Although the FORM + KI and FORM + PVP-I combinations enhanced the efficacy of aPDT in inactivating MRSA in PBS, this effect was not observed in ex vivo assays. Overall, aPDT using FORM as PS, even without adjuvants, is a promising therapy for the inactivation of MRSA on skin.